First record of the genus Setelacher Bouček (Hymenoptera: Eulophidae: Eulophinae) from the Afrotropical region, with description of a new species. Issue 9 (18th March 2020) - Gumovsky, Alex; Bazhenova, Tetyana; van Noort, Simon
ABSTRACT: A new species of the genus Setelacher Bouček, S. lasallei sp. nov. Gumovsky and van Noort, is described from the Afrotropical region (Central African Republic, Gabon and Uganda). It confirms the presence of the genus in the region. The only described species of the genus, S. fasciatus Bouček, is of Australasian and Indo-Malayan distribution, and one undescribed species was previously recorded from South Africa. All images presented here are available on www.waspweb.org http://www.zoobank.org/urn:lsid:zoobank.org:pub:D6AA0B15-6EA7-4C93-827C-1807E69BD6D2